Description of a new whitefly genus and two new species (Hemiptera: Aleyrodidae) from the Western Ghats and Andaman Islands, India - Dubey, Anil Kumar (Zootaxa, 2024)
Cerafilum gen. nov. is described for Cerafilum ochlandrae sp. nov. and Cerafilum saddlense sp. nov., from India and colonising bamboo species. Cerafilum gen. nov. is compared with the allied genus Aleuromarginatus Corbett and Setaleyrodes Takahashi and diagnoses and illustrations provided, including habitus, line drawings of holotype, diagnostic characteristics, types’ images and scanning electron microscope microphotographs.